A multi-method approach to understanding behavior change : the case of texting and driving - Karen M. Hood; Christine M. Kowalczyk; Christopher D. Hopkins; Daniel Padgett (Expert journal of marketing, 2017)
Distracted driving, specifically texting and driving, has become a nationwide public health problem in the U.S. with negative, and potentially fatal consequences. In an effort to combat the growing problem, non-profit organizations, corporations, and the federal government have all stepped in to try to increase public awareness and persuade drivers to cease texting while driving. These efforts have not had the desired impact as texting and driving has continued to increase in recent years. This research investigates the potential that the messages used to curb texting and driving behavior might not be properly constructed. Specifically, we test the potential for message sponsor and self-relevance of the message to influence message outcomes. Our results suggest that messages sponsored by a combination of company and government that are self-relevant to viewers will have different outcomes than other messages. We identify practical and theoretical implications as well as future research directions.
2758454-9; 2344-6773; Expert journal of marketing; 778946770